Tantangan Literasi Digital dan Dampaknya terhadap Pemanfaatan Pembayaran Digital : Kajian Literatur - Afif Julian Syaputra; Muhammad Alfarizi; Muhamad Bayu Irawan; Muhammad Ilham (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This The development of the digital economy has brought significant changes to payment systems, including a shift from cash to digital payment methods. However, the optimal adoption and utilization of digital payments still face various challenges within society. This study aims to analyze the efficiency of digital payment systems and their impact on economic actors. Using the Systematic Literature Review (SLR) method, this research finds that digital payments can reduce transaction time and costs compared to conventional methods such as cash. Furthermore, the results confirm that digital payments provide significant convenience for economic actors. The primary focus of this research is the role of financial technology (fintech) for market participants, particularly Micro, Small, and Medium Enterprises (MSMEs), in adopting a new lifestyle based on digital payment technology. This study provides a vital contribution to enhancing the understanding of the impact of digital payments on economic actors and the shift in consumer behavior in today's digital era.